Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Cosec theta - cot theta =x then find cosec theta + cot theta

Cosec theta - cot theta =x then find cosec theta + cot theta

Grade:10

1 Answers

sreya c
23 Points
4 years ago
let theta=y
we have an identity that is cosec^2(Y)-cot^2(Y)=1
therefore using it we can find the answer
cosec^2(Y)-cot^2(Y)=1
[cosec(Y)+cot(Y)][cosec(Y)-cot(Y)]=1            {since a^2-b^2=[a+b][a-b]}
[cosec(Y)+cot(Y)][x]=1                                 {from given}
cosec(Y)+cot(Y)=1/x

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free